Validation and Characterization of TCF7L1-SALL4 Protein-Protein Interaction in Mouse Embryonic Stem Cells - Seo, Caleb (My University, 2019)
Here, we validate novel protein interactors of TCF7L1 (also known as TCF3), a downstream transcription factor in the Wnt/β-catenin signaling pathway, from an initial protein interaction screen that utilized the BioID system in mouse embryonic stem cells. The BioID-TCF7L1 screen identified multiple proteins including several transcription factors and numerous epigenetic regulators. Notably, SALL4, a key embryonic stem cell factor belonging to the SPALT family of transcription factors was validated to interact with TCF7L1 through Proximity Ligation Assay (PLA), and Co-Immunopreciptation (Co-IP). Analysing mRNA transcriptomic signatures of TCF7L1-null mEScs and SALL4 overexpressing mESCs, we observed similarly increased output of the pluripotency-gene, Tbx3, suggesting a transcriptionally opposing function between TCF7L1 and SALL4. Furthermore, we identified that SALL4 also interacted with TCF7, suggesting that SALL4 may interact with all four members of the TCF/LEF transcription factor family to regulate Wnt targets. This work further validates the utility and effectiveness of screening transcription factor interactors through the BioID system and provides important insights into SALL4 mediated Wnt regulation through the TCF/LEFs.
Keywords: mESC Embryonic Stem Cells TCF7L1 SALL4 Wnt Signaling Cell Biology Protein-Protein-Interaction Protein Co-IP PLA qPCR